Intrasphenoidal Rathke Cleft Cyst - Megdiche-Bazarbacha, H.; Ben Hammouda, K.; Aicha, A.B.; Sebai, R.; Belghith, L.; Khaldi, M.; Touibi, S. (American Journal of Neuroradiology, 2006)
SUMMARY: Symptomatic Rathke cleft cysts (RCC) are reported in the sellar and suprasellar regions, but no case of sphenoidal RCC has been reported. We report a case of sphenoidal RCC in a 41-year-old man. The lesion was revealed by headaches and diplopia. Symptoms disappeared transiently after a spontaneous rhinorrhea but relapsed 4 months later. MR imaging showed a cystic sphenoidal lesion, isointense on T1-weighted images (WI) with peripheral gadolinium enhancement and hyperintense on T2 WI. The patient underwent surgery through a transrhinoseptal approach. The wall of the sphenoid sinus was paper-thin. The cyst contained a motor-oil-like fluid and communicated widely with the nasal fossa. Its wall was partially extracted. Symptoms and signs ceased after surgery. MR imaging performed 1 year later showed the disappearance of the sphenoidal cyst. Embryological origin of RCCs is discussed. The hypothesis of a continuum between the different epithelial cystic lesions of the sellar and parasellar region is discussed. Imaging has an important impact on the diagnosis; nevertheless, the specific characterization remains difficult.